Developing Sustainable Smart Cities to Improve Citizen's Quality of Life and Well-Being - Berawi, Mohammed Ali; Sari, Mustika; Miraj, Perdana (UI Scholars Hub, 2023)
In the wake of urbanization and environmental challenges, cities nowadays face multiple issues related to uncontrolled urban growth, insufficient public infrastructure, and inadequate citizen participation in the management of public affairs. Sustainable urban development cannot be achieved without addressing these challenges, necessitating a paradigm shift in urban space management. Therefore, urban development needs to shift traditional concepts and focus on incorporating smart and environmentally friendly practices that allow cities to adapt and implement intelligent solutions to meet the needs of their citizens while continuing to protect the environment. To achieve sustainability, cities should prioritize a balance between economic activity, population growth, urban infrastructure development, and urbanization. Promoting sustainability in urban social, economic, and ecological domains requires the inclusion of technology advancement, supported by people's participation, into urban planning policies and practices through smart city development. Smart cities are gaining recognition as transformative urban environments that leverage technology and data to enhance the quality of life for citizens. While the concept primarily focuses on efficiency, sustainability, and connectivity, the profound impact on citizens' happiness and overall well-being cannot be understated. The concept of a smart city should be a citizen-centric approach that places the well-being and happiness of citizens at its core. Innovative technologies and data-driven solutions can allow cities to meet the specific needs of their inhabitants. From efficient transportation systems and accessible healthcare to smart governance and inclusive public spaces, citizen-centric smart cities foster a sense of belonging and empowerment. Smart cities hold immense potential to improve the citizens' quality of life. The seamless integration of advanced technology into urban infrastructures allows decision-making to optimize resource allocation, provide public safety, and offer convenient services for the people. For example, smart utilities such as efficient energy management and automated waste disposal can contribute to a cleaner and more sustainable environment, positively impacting physical and mental well-being. Moreover, smart healthcare systems can offer personalized and timely medical services, ensuring better health outcomes for citizens. In addition, smart cities can improve citizens' access to real-time information, collaboration platforms, and engagement with fellow community members. Digital platforms and smart urban design can further boost citizens' engagement in decision-making processes, fostering a sense of community and public participation. Subsequently, smart cities inherently promote sustainability by optimizing resource management, reducing energy consumption, and endorsing eco-friendly practices. Cities like Singapore and Amsterdam have implemented smart infrastructure and utilize renewable energy, such as water-based and wind-based technologies, to minimize their environmental footprint while ensuring a resilient future by implementing smart infrastructure and renewable energy sources. The inclusion of green spaces, pedestrian-friendly zones, and efficient public transportation systems may contribute to citizens' physical and mental well-being, fostering vibrant and sustainable communities. Despite the importance of focusing on the positive aspects of smart cities, it is also essential to be aware of any potential issues. Concerns regarding data privacy, the technological gap, and the prospect that technology will exacerbate social differences must be addressed in advance to ensure the sustainability of smart city development.